THE EFFECTS OF DIFFERENT STORAGE TEMPERATURES AND TIME ON THE SURVIVAL OF CPE (+) CLOSTRIDIUM PERFRINGENS TYPE A IN ÇİĞ KÖFTE (A TRADITIONAL TURKISH RAW MEAT PRODUCT) - Güran, Hüsnü Şahan; İlhak, Osman İrfan (My University, 2015)
This study was carried out to investigate the survival of cpe (+) Clostridium perfringens type A in çiğ köfte. For this purpose, çiğ köfte samples were artificially contaminated with the pathogen, and then the samples were stored at 4, 24 and 30ºC for 72 h. The numbers of cpe (+) Clostridium perfringens type A, total aerobic mesophilic bacteria (TAMB) and lactic acid bacteria (LAB) in the samples were analysed at 6, 12, 24, 48 and 72 h of storage. The number of the pathogen in the samples stored at 30ºC significantly decreased during the storage and dropped below detection level (10 cfu/g) after 48 h while the reduction number of the pathogen in the samples stored at 4ºC was 1.60 log cfu/g at the end of the 72 h. The numbers of the TAMB and LAB in the samples stored at 24ºC and 30ºC rapidly increased compared to the samples stored at 4ºC during the storage period (P<0.05). This study demonstrates that this pathogen can survive in çiğ köfte stored at refrigeration temperature for more than 3 days, but cannot survive at 30ºC for 3 days.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: cpe (+) C. perfringens type A; temperature; çiğ köfte; survival